P166 Identifying low hanging fruit for worker safety: results from a worker survey in qatar. (1st September 2016) - Consunji, Rafael; Peralta, Ruben; Al-Thani, Mohammed Hamad; Al-Hajjaj, Mohammed Ali Mohammed; Thomas, Sam; El-Menyar, Ayman; Al-Thani, Hassan
Abstract : Qatar is a rapidly developing country in the Arabian Gulf. This growth is fueled by the over 80% of its population that work as migrant workers, Information on the risk factors for occupational injuries in this population is needed.This survey was conducted during the Supreme Council of Health World Day for Safety and Health at Work, to identify the work related injuries and risk factors for workers in various industries. 262 workers were interviewed using a standard questionnaire, none refused interview. Nurses and doctors from the Hamad Trauma Centre conducted the interviews. Questions were translated into the workers native language when it was needed. Males made up 98% of all respondents. The main occupations were: construction workers of 53% and transportation workers 12%. The majority were from Nepal, India and Bangladesh. The percent who could read English was 64% and speak English was 80%. Those who could read Arabic was 5% and speak Arabic was 10%. The mean duration in Qatar was 24 months and mean age was 33.4 years. One in five had no formal schooling, 60% were secondary school graduates, and only 3% had college degrees. Only 6.4% of the workers declared a WRI in the last 12–24 months. No statistically significant differences were noted between the group injured when compared to those not injured. Further research is needed to identify risk factors for worker injury in Qatar. Acknowledging language barriers and creating safety education targeted to key populations and appropriate literacy levels should be implemented in future occupational safety initiatives in Qatar.